Analisis Elemen Hingga Lapisan Tanah Menggunakan Geotekstil Sebagai Metode Perbaikan Tanah Lunak Dengan Software Plaxsis: Finite Element Analysis Of Soil Layers Using Geotextiles As A Soft Soil Improvement Method With Plaxsis Software - Indriani, Lilis (Media Ilmiah Teknik Sipil, 2025)
The case of embankment on soft clay soil that must be completed quickly can be assisted by additional reinforcement on the soft soil. One example is by using geosynthetics that have high tensile strength at the base of the embankment, thereby increasing the stability of the embankment. The use of geosynthetics is widely used in the improvement of soft clay subgrade in embankment construction in an effort to increase its bearing capacity. The purpose of this study was to determine the effect of the use of geotextiles under embankment soil to increase the stability of the soil below it and to determine the safety value, deformation and stress changes that occur in soil reinforced with geotextiles using Plaxis 2D software. The methods used in this final project consist of data collection methods, data analysis techniques, presentation methods and flow diagrams of planning studies. From the results of the analysis, the safety factor is F = 0.742 <1.2 for embankment conditions without geotextiles while the safety factor is F = 1.380> 1.2 for embankment conditions with geotextiles. This shows that there is an effect of using geotextiles under the embankment in increasing the safety factor. The total deformation value for embankments without geotextiles is 25.10 mm, the total stress value for embankments without geotextiles is 180.35 kN/m2, the total deformation value for embankments with geotextiles is 36.27 mm, while the total stress value for embankments with geotextiles is 190.26 kN/m2.